The Effect of Parity, Birth Weight Babies, Pregnancy Interval and a History Of Hemorrhage with The Incidence of Postpartum Hemorrhage - Izfa Rifdiani (Jurnal Berkala Epidemiologi, 2016)
Postpartum hemorrhage is one of the problems that cause maternal deaths in Indonesia. The maternal mortality rate is one indicator to see the degree of health of a woman in particular, society in general. This study aims to analyze the effect of parity, birth weight, pregnancy gap, and history of postpartum hemorrhage in mothers after childbirth to the incidence of postpartum hemorrhage at Regional Public Hospital (RSUD) Ngudi Waluyo Wlingi Blitar in 2014. This study used a case-control design. The study population was all mothers who childbirth at RSUD Ngudi Waluyo Wlingi in Blitar in 2014. The sampling technique was using simple random sampling. The results showed that there was an effect of the pregnancy gap (OR = 17,953; 95% CI = 3,550–90,785) and history of postpartum hemorrhage (OR = 18,104; 95% CI = 3,559–92,097) on the incidence of postpartum hemorrhage. There was no effect between parity 2-3 times (OR = 0.810; 95% CI = 0.329-1995) or ≥4 times (OR = 0.895; 95% CI = 0.260-3.077) and birth weight (OR = 0.651; 95% CI = 0.104-4.096) of the incidence of postpartum hemorrhage. Health workers are expected to provide advice to mothers delivery to participate in a family planning program so that pregnancy spacing can be well managed. Checking the accuracy of visits of pregnant women each semester will make health workers, pregnant women, and families more monitored for the possibility of postpartum hemorrhage after childbirth.